2017
DOI: 10.1002/bse.1973
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Stakeholders' Voice: The Effects of Social Media Activism on Stock Markets

Abstract: Building on social movement theory, this study assesses the influence of social media activism on the stock market performance of targeted firms. We focus on information published on Twitter by two critical stakeholders: consumer associations and trade unions. To the extent that social media represent a valid medium to mobilize stakeholders' activism, protests on Twitter may damage firm reputation, leading to capital market reactions. Using a corpus of over 1.5 million tweets referring to Spanish listed banks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 82 publications
(94 reference statements)
1
54
0
2
Order By: Relevance
“…Servaes and Tamayo () find that CSR awareness among the public can have a positive effect on firm value. Gomez‐Carrasco and Michelon () also document that Twitter activism of key stakeholders has a significant impact on investors' decisions, and that organisations affect investors' decisions through their visibility. Thus, SVI is also included as a control variable; Drake et al () use SVI as a proxy for investor attention for the company in the stock market.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Servaes and Tamayo () find that CSR awareness among the public can have a positive effect on firm value. Gomez‐Carrasco and Michelon () also document that Twitter activism of key stakeholders has a significant impact on investors' decisions, and that organisations affect investors' decisions through their visibility. Thus, SVI is also included as a control variable; Drake et al () use SVI as a proxy for investor attention for the company in the stock market.…”
Section: Discussionmentioning
confidence: 99%
“…Doluca, Wagner, and Block () investigate the relationship between family firms, environment and social responsibility, and find that family firms are less likely than other firms to implement environment‐related activities and innovations in early diffusion phases, but catch up with non‐family firms later. Gomez‐Carrasco and Michelon () investigate how social movements influence corporate behaviour via social media and find that the Twitter activism of key stakeholders has a significant impact on investors' decisions. Using information published on Twitter in a different manner to Gomez‐Carrasco and Michelon (), this study focuses on Google Search Volume Index (SVI) data for firms' abbreviated name and stock identification codes as measures of investor attention proxy for each specific company.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Businesses are often challenged by social movements. For example, Gomez‐Carrasco and Michelon () found that social media activism of key stakeholders powerfully influences investors’ decisions and stock markets. Shareholder activism is a significant part of activism that can influence business strategy.…”
Section: Shareholder Activism and Shareholder Activists’ Networkmentioning
confidence: 99%
“…However, despite numerous empirical analyses of textual contents of CSR websites and Twitter (e.g., Araujo & Kollat, 2018;Gomez-Carrasco & Michelon, 2017;Tang et al, 2015;Vollero, Conte, Siano, & Covucci, 2019), the same empirical insight is not available for images on the same channels. This paper aims to fill this gap with a particular focus on the comparison between owned and shared media (Macnamara et al, 2016) While automated methods for text analysis have been employed for quite some time (Boumans & Trilling, 2016), the same method has not been available for large amounts of images.…”
mentioning
confidence: 99%